Padu Padan Kebutuhan dan Pengembangan Koleksi Perpustakaan Universitas Wijaya Kusuma Surabaya - Yanuastrid Shintawati; Bambang Prakoso; Daniel Pandapotan; Bakhtiyar; Dian Kristyanto; Fahriyah (Pustabiblia: Journal of Library and Information Science, 2026)
This study aims to analyze the collection development policy at the Library of Universitas Wijaya Kusuma Surabaya in response to the evolving information needs of academic communities and scientific advancement. The research focuses on identifying managerial strategies in user-oriented collection development. A qualitative approach was employed, with data collected through in-depth interviews, participatory observation, and document analysis, validated using source triangulation. The findings reveal that the library implements its policy through user needs analysis, thematic priority setting, adaptive budgeting, and collaboration with faculties and publishers. The use of digital library management systems and user surveys supports the relevance and efficiency of the selection and evaluation process. The main contribution of this study lies in formulating strategic, user-driven practices that can be replicated by other academic libraries as a model for dynamic and sustainable collection development.